2010
DOI: 10.1186/1471-2164-11-180
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing in an ecologically important tree species: assembly, annotation, and marker discovery

Abstract: BackgroundMassively parallel sequencing of cDNA is now an efficient route for generating enormous sequence collections that represent expressed genes. This approach provides a valuable starting point for characterizing functional genetic variation in non-model organisms, especially where whole genome sequencing efforts are currently cost and time prohibitive. The large and complex genomes of pines (Pinus spp.) have hindered the development of genomic resources, despite the ecological and economical importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
348
10
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(410 citation statements)
references
References 67 publications
(132 reference statements)
46
348
10
6
Order By: Relevance
“…This final dataset was then subjected to putative functional annotation using a more rigorous blastx search (E value < 10 -10 ) against the NCBI non-redundant (nr) protein database. The length of contigs was significantly correlated with the number of sequences assembled into them (Pearson ρ = 0.53; n= 20,938; p < 0.0001), as expected for 454 reads (Parchman et al, 2010) and the size distribution of contigs resembled that of previous 454 studies (Bettencourt et al, 2010;Fraser et al, 2011;Hou et al, 2011) (Supplementary Figures S1A and S1B). Files containing the reads have been submitted to the National Center for Biotechnology Information Short Read Archive [GenBank: SRX790900].…”
Section: Sequencing and De Novo Assembly Of The Oyster Transcriptomesupporting
confidence: 55%
“…This final dataset was then subjected to putative functional annotation using a more rigorous blastx search (E value < 10 -10 ) against the NCBI non-redundant (nr) protein database. The length of contigs was significantly correlated with the number of sequences assembled into them (Pearson ρ = 0.53; n= 20,938; p < 0.0001), as expected for 454 reads (Parchman et al, 2010) and the size distribution of contigs resembled that of previous 454 studies (Bettencourt et al, 2010;Fraser et al, 2011;Hou et al, 2011) (Supplementary Figures S1A and S1B). Files containing the reads have been submitted to the National Center for Biotechnology Information Short Read Archive [GenBank: SRX790900].…”
Section: Sequencing and De Novo Assembly Of The Oyster Transcriptomesupporting
confidence: 55%
“…Compared with Wang et al (2010b), in which only 16.2% had BLAST hits in Nr database, the higher percentage in the present study was partially ascribed to the higher frequency of long sequences (Wang et al, 2010b). As reported by Parchman et al (2010), longer contigs were more likely to have BLAST matches in the protein database.…”
Section: Functional Annotation By Searching Against Public Databasessupporting
confidence: 55%
“…These unigenes had a mean length of 580 bp (Table 1). Our data indicated that the C. nasus unigenes were roughly shorter than the average lengths of unigenes that were previously reported in other species such as Eriocheir sinensis (382 bp) (He et al, 2012), Acropora millepora (440 bp) (Meyer et al, 2009), Pinus contorta (500 bp) (Parchman et al, 2010), Chlamydomonas spp (665 bp) (Kim et al, 2013), and Camellia sinensis (733 bp) (Wu et al, 2013). These results provide sequence information for future gene cloning and transgenic engineering stud ies.…”
Section: Illumina Sequencing and Assembly Of The Transcriptomementioning
confidence: 60%
“…Next-generation sequencing (NGS) technologies facilitate generation of a large number of sequences and have been used recently to isolate simple-sequence repeat (SSR) markers in studies of non-model animals, plants, and fish (Parchman et al, 2010). Transcriptome sequencing can yield a subset of genes from the genome that are functionally active in a selected tissue and species of interest (Venter et al, 2001;Martinez-Alcantara et al, 2009;Metzker, 2010;Schatz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%